Locating African Identity in Postcolonial African Discourse: A Postcolonial Analysis of Chinua Achebe’s Things Fall Apart and Arrow of God - Zahid Abbas; Muhammad Tufail Chandio (University of Chitral Journal of Linguistics and Literature, 2024)
The study analyses the African identity portrayed in Achebe’s novels Things Fall Apart (1958) and An Arrow of God (1964) from the vantage point of the postcolonial theoretical perspective or Postcolonial African identity Discourse of Frantz Fanon. Twenty-first-century Africa is a diverse continent, especially when looked at from the perspective of post-colonialism, where various groups of people exist. Because of past colonial residue and experience, the governments in the region are still divided, and people live with fragmented identities. The continent has undergone drastic changes before and after its independence. In this regard, the study of postcolonial African literature seems to be incomplete without the study of the African colonial past and the ideologies emerging from this part of the world. In this regard, Chinua Achebe is one of the prominent writers of African literature who presents the glaring picture of African culture by celebrating its identity as self-sufficient. He introduces the reader to the critical contextualizing historical and cultural perspectives of African history and identity. The novels written by Achebe not only depict the history and culture of Africa but also serve as a direct response to the whole canon of Eurocentric writings in which African race, history, culture, religion, and society have been misrepresented as inhuman and savage, which are nothing but false constructs when viewed from a ppostcolonialperspective. His novels, mainly Things Fall Apart and An Arrow of God, paint a grim picture of the colonization of Nigeria in particular and the African continent in general. He illustrates various ways of representing the self-sufficiency of African nations with a strong sense of African identity.